Mediating Impact of Fashion Consciousness on the Cosmopolitism and Fashion-Oriented Lifestyle of Young Fashion Consumers in Sri Lanka - Jayarathne, P. G. S. A. (My University, 2019)
The importance of knowledge about consumer behaviour in the fashion industry is felt now more than any other time. Fashion oriented lifestyle is identified as a significant aspects of consumer behaviour in the fashion industry. Fashion consciousness is also a central aspect of the self of the fashion consumer; and cosmopolitanism has also become an integral part of social systems. Thus, cosmopolitanism may become one of the key determinants of fashion consciousness in the world at large despite the geographical proximity and may consequently influence the fashion-oriented lifestyle. Although scholars have paid their attention around this area, none of them has studied the relationship among fashion consciousness, cosmopolitism and fashion-oriented life style at once. Addressing such gap in the literature, this study aims to examine the mediating impact of fashion consciousness on cosmopolitism and fashion oriented lifestyle of young consumers in the fashion industry in Sri Lanka. A survey is carried out with 458 structured questionnaires taking the individual young consumers of fashion products in Sri Lanka as the unit of analysis. The result uncovers that the fashion consciousness fully mediates the relationship between cosmopolitanism and fashion-oriented lifestyle of the young fashion consumers. Finally the paper makes important implications and suggestions for practitioners as well as for academics in the field of fashion and fashion related products.
Keywords: Cosmopolitism; Fashion Consciousness; Fashion Oriented Lifestyle